Diagnostic Value of Non-Contrast CT in Cerebrospinal Fluid Leakage After Endoscopic Transnasal Surgery for Sellar and Suprasellar Tumors - Gao, Wei; Wang, Xiaoyu; Fang, Yuanjian; Hong, Yuan; Yan, Wei; Zhang, Sheng; Li, Chenguang (Frontiers in Oncology, 2022)
Abstract To study the relationship between pneumocephalus on non-contrast CT (NCCT) and post-operative cerebrospinal fluid leakage (p-CFL) after endoscopic transsphenoidal sellar and suprasellar tumor surgeries. Data from patients who underwent endoscopic treatment for sellar or suprasellar tumors from January 2018 to March 2020 were consecutively collected and reviewed. The NCCT pneumocephalus (NP) was measured the first day after operation and the first day after expansive sponge was extracted. p-CFL was determined according to post-operative clinical symptom, high resolution CT and glucose test, and expert consensus. Of 253 patients enrolled in this study, 32 (12.6%) were identified as p-CFL. Compared with patients without p-CFL, patients with p-CFL had a higher occurrence of intra-operative CFL, a longer operation time, a higher rate of pneumocephalus on first-day NCCT after operation (i.e., first-day NP), and a higher rate of NP volume change between two NCCT measurements (referred to as the NP change) (all P<0.05). In multivariate regression analysis, first-day NP was independently associated with p-CFL occurrence (odds ratio [OR]=6.176, 95% confidence interval [CI]=2.134–17.871, P=0.001). After adding the NP change into the regression model, first-day NP was no longer independently associated with p-CFL, and NP change (OR=21.192, 95% CI=6.292–71.373, P<0.001) was independently associated with p-CFL. The receiver operating characteristic curve comparison analysis showed that NP change had a significantly better predicting value than first-day NP (area under the curve: 0.988 vs 0.742, Z=6.451, P=0.001). NP is an effective imaging marker for predicting p-CFL after endoscopic sellar and suprasellar tumors operation, and the NP change has a better predicting value.